Sharing is indeed caring - Nur Syafawati, Sabuan; Rosjuliana Hidayu, Rosli; Hanisah, Kasbon (Pusat Bahasa Moden (PBM), 2021)
On 24 March 2021, a video editing class was successfully arranged for Kelas Al-Qur’an dan Fardhu Ain (KAFA) teachers at the Islamic and Human Development Centre, UMP. The class focused on the introduction to Kinemaster application to be utilised by the KAFA instructors to assist them in producing more comprehensive teaching and learning materials. Other than that, the instructors were also familiarised with chroma-key editing involving video production technique compositing procedures and effective ways to create high quality videos.